Investigation of side reactions during the conventional radical polymerisation of maleic anhydride and n-butyl vinyl ether - Chagwedera, Ruvimbo Michelle (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.